Correlation of violence with anxiety and sleep disturbance among Talibs (mosque students) in Afghanistan: A cross-sectional study - Ahmad Neyazi; Abdul Qadim Mohammadi; Nosaibah Razaqi; Prakasini Satapathy; Qasim Mehmood; Mehrab Neyazi (Sleep Epidemiology)
Background: Despite ample research on violence's impact on mental health, a literature gap persists regarding its specific influence on anxiety and sleep quality among mosque students, particularly Talibs, in Afghanistan. This study examines the influence of violence on anxiety levels and sleep quality among mosque students, specifically Talibs, in Afghanistan. Methods: This cross-sectional study administered between March 10, 2023 to June 25 2023, among Talibs (mosque students) across Herat province of Afghanistan. Data were collected using a pretested structured questionnaire. The Pittsburgh Sleep Quality Index (PSQI), and anxiety subscale of the Depression, Anxiety, Stress – Youth (DASS-Y) questionnaire was used to assess sleep quality and anxiety among Talibs. Logistic regression models were used to examine the association of violence, anxiety, and sleep disturbance, and socio-demographic characteristics among Talibs (N = 378). Results: Prevalence rates for anxiety symptoms, sleep disturbances, and experiences of violence were 47.9 %, 29.1 %, and 79.6 %, respectively. Notably, anxiety symptoms in Talibs exhibited correlations with advanced age and exposure to violence. Multiple regression analysis revealed significant associations between father's education, violence exposure, and anxiety, while age, economic status, and parental employment correlated with sleep disturbances. Conclusion: Given the impact of violence on anxiety and sleep quality, this study recommends routine screening for anxiety and sleep disturbances by authorities and health organizations. Psychological counseling services should be available for vulnerable Talibs. Enforcing a prohibition against violence within mosque settings could alleviate anxiety symptoms and sleep disturbances among this population.